FORMALIZED HANDWRITING ANALYSIS AS A COMPLEMENTARY TOOL IN FORENSIC PSYCHOLOGICAL ASSESSMENT - Chernov, Yury; Aghuzumtsyan, Ruben (Modern Psychology, 2025)
Forensic psychological assessment demands a comprehensive, scientifically grounded approach capable of capturing both explicit behavior and implicit psychological dynamics. This article explores the role of formalized handwriting analysis as a structured projective method that complements traditional tools within a multimodal forensic framework. The approach relies on standardized definitions, measurable handwriting parameters, and statistical modeling to translate observable motor patterns into psychologically meaningful indicators.By focusing on measurable or at least quantitatively assessed handwriting features, such as spatial layout, pressure, speed, form, rhythm, and variability, the method provides access to implicit emotional and cognitive dynamics that are often inaccessible through self-report or structured testing. Its unobtrusive and natural character makes it particularly effective in forensic contexts, where examinees may consciously attempt to regulate or distort self-presentation.Although empirical validation remains an ongoing process, each application contributes to the refinement and confirmation of model reliability. Case-based analyses demonstrate that handwriting indicators can align meaningfully with expert psychological judgments and behavioral observations, while occasional discrepancies help refine interpretation and promote diagnostic caution. Through methodological triangulation, this approach supports the integration of implicit and explicit data, enhancing both the depth and the objectivity of forensic conclusions.Formalized handwriting analysis, when applied within a multimethod design, supported by AI-methods and interpreted by qualified professionals, offers an additional layer of insight into personality structure and behavioral regulation. Its systematic and transparent use reinforces the scientific validity and legal defensibility of expert psychological evaluations, contributing to more comprehensive and credible forensic assessments.
Keywords: forensic; handwriting analysis; formalization; case-study; projective techniques; artificial intelligence